1)75/9=9/x;
x=9*9/75=(3*3*9)/(3*25)=27/25;
2)x/0,75=1,4/0,25;
x=(0.75*1.4)/0.25=4.2
3)2,5/1,25=8/x;
x=(8*1.25)/2.5=4
4)(3+1/3)/(2+2/9)=1,2/x;
(10/3)/(20/9)=(6/5)/x;
x=(20/9*6/5)/(10/3)=(3*20*6)/(9*5*10)=(3*2*10*3*2)/(3*3*5*10)=4/5
<span>30+x>40
х</span>>40-30
х>10
<u>Ответ: х>10</u>
Ответ:
A - С = B
Пошаговое объяснение:
Чтобы A (сумму) нужно С + B. Следовательно С и b можно найти за такими формулами:
С = A - b
B = A - C
17,8*6=106,8
106.8/17=6,28 округляем до 6.3
25/6=4,16 округляем до 4,2
4,2*6,3=26,46
Если не округлять то ответ будет 26.1248